Consulting report Team 2- MASEDI Contratistas Generales - Bayer, Sofie Barbara; Huemura Okumura, Daniel Keiichi; Núñez Acevedo, Sary Mishel (Pontificia Universidad Católica del Perú, 2021)
MASEDI is a Peruvian construction company created and founded by Vladimir Sokolic in 1999. They provide services in the field of architectural design, construction, maintenance and everything related to the area. Its approach as a company is based on leadership, experience, quality and personalized service in each project. The main problem identified is the low brand awareness which prevents from obtaining a greater number of clients in the private sector. This is mainly due to the strong competition, lack of a marketing department to promote the brand, as well as the reliance on word of mouth advertising thanks to its good reputation in the public sector. In that sense, the CEO is interested in finding strategies to make MASEDI recognized in the private sector for its quality service and expertise. The theory reviewed to develop the solution to the problem suggests marketing strategies through social media and content management; customer relationship management (CRM); and corporate social responsibility activities (CSR). Then, four alternatives were developed and evaluated regarding to cost, feasibility, effectiveness, ease of implementation and reliability. The final proposal includes an integrated marketing communication strategy through digital and nondigital media, as well as the division of the client portfolio, whose implementation plan is detailed step by step for MASEDI, in order to obtain new clients, get brand recognition and increased traffic on the web and social networks.

MASEDI es una empresa constructora peruana creada y fundada por Vladimir Sokolic en 1999. Brindan servicios en el ramo del diseño arquitectónico, construcción, mantenimiento y todo aquello concerniente al rubro. Su enfoque como empresa se basa en el liderazgo, experiencia, calidad y servicio personalizado en cada obra. El principal problema identificado es el bajo reconocimiento de marca lo cual impide obtener un mayor número de clientes en el sector privado. Esto se debe principalmente a la fuerte competencia, inexistencia de un departamento de marketing que promueva la marca, así como la dependencia de publicidad boca a boca gracias a su buena reputación en el sector público. En ese sentido, el CEO está interesado en la búsqueda de estrategias para que MASEDI sea reconocida tanto en el sector privado por su servicio de calidad y experiencia. La teoría revisada para desarrollar la solución al problema sugiere estrategias de marketing mediante redes sociales y administración de contenido; gestión de relación con clientes (CRM) ; y actividades de responsabilidad social (CSR). Luego se desarrollaron cuatro alternativas las cuales fueron evaluadas en cuanto al costo, factibilidad, efectividad, facilidad de implementación y confiabilidad. La propuesta final comprende una estrategia de comunicación de marketing integrada a través de medios digitales y no digitales, así como la división del portafolio de clientes, cuyo plan de implementación se detalla paso a paso con el fin de que MASEDI obtenga nuevos clientes, reconocimiento de marca y un mayor tráfico en la web y redes sociales.
Keywords: Consultores de empresas; Planificación estratégica; https://purl.org/pe-repo/ocde/ford#5.02.04